A positive electrode material and its preparation method and application

The preparation of sodium vanadium phosphate composite carbon nanofiber material through electrospinning technology and forming an M2Ox mesogenic cladding layer, solving the problem of low electronic conductivity of sodium vanadium phosphate material and significantly improving its rate performance and cyclic stability.

CN116190666BActive Publication Date: 2025-02-07JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310488820.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-04
Publication Date
2025-02-07
Estimated Expiration
2043-05-04

AI Technical Summary

Technical Problem

As the cathode material of sodium ion batteries, sodium vanadium phosphate (NVP) has low electronic conductivity, which affects its electrochemical performance.

Method used

The sodium vanadium phosphate composite carbon nanofiber material was prepared by electrospinning technology, and an M2Ox mesogenic cladding layer was formed on its surface to improve the conductivity and structural stability of the material.

Benefits of technology

It effectively improves the rate performance and cycle stability of the material, stabilizes the sodium vanadium phosphate material during the charging and discharging process, and improves its electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116190666B_ABST
    Figure CN116190666B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode material and a preparation method and application thereof. The positive electrode material of the present invention comprises a sodium vanadium phosphate composite carbon nanofiber material and a conductive mesogen coating layer coated on the surface of the sodium vanadium phosphate composite carbon nanofiber material. 2 Ox mesomorphous material coated with carbon composite sodium vanadium phosphate nanofiber material M 2 O x @NVP / C stabilizes the sodium vanadium phosphate during the charge and discharge process on the basis of enhancing the ionic conductivity and electronic conductivity of sodium vanadium phosphate, thereby improving the rate charge and discharge performance and cycle stability of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium vanadium phosphate (Na3V2(PO4)3, NVP for short) is a typical polyanion type sodium ion battery cathode material. Due to its unique sodium ion superconductor (NASICON) structure, it has high ionic conductivity and excellent structural stability. It is a sodium ion battery cathode material with great application prospects. However, this material also has obvious shortcomings. The presence of the [PO4] tetrahedral structure will hinder the transmission of electrons in the material, resulting in very low electronic conductivity, which will further restrict the reaction kinetics of the material and affect the electrochemical performance of the material. Therefore, it is necessary to improve its electrochemical performance. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a positive electrode material and a preparation method and application thereof.

[0004] The present invention is achieved through the following solutions:

[0005] The first object of the present invention is to provide a method for preparing a positive electrode material, comprising the following steps:

[0006] A sodium source, a vanadium source, a phosphorus source, a high molecular polymer, a carbon source and a solvent are mixed to obtain an electrospinning solution, and electrospinning is performed to obtain a nanofiber precursor, and a heat treatment is performed to obtain a sodium vanadium phosphate composite carbon nanofiber material;

[0007] The salt or oxide containing M is dispersed in an acid solution, the obtained mixed solution is reacted at 100°C to 200°C, and the reaction liquid is separated into a solid phase, which is M2O x Mesogenic materials;

[0008] The sodium vanadium phosphate composite carbon nanofiber material and the M2O x Mesogen materials are mixed and subjected to secondary heat treatment to form M2O x Mesogen coating layer to obtain the positive electrode material;

[0009] Wherein, M is one or more of Zn, Ce, Ti, Cu, Fe, W, Pb and Cd, and x is the valence state of M.

[0010] In one embodiment of the present invention, the sodium source can be selected from conventional materials in the art, preferably but not limited to one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate and sodium nitrate;

[0011] In one embodiment of the present invention, the vanadium source can be selected from conventional materials in the art, preferably but not limited to one or more of vanadium powder, vanadium pentoxide, vanadium trioxide and ammonium metavanadate;

[0012] In one embodiment of the present invention, the phosphorus source can be selected from conventional materials in the art, preferably but not limited to one or more of diammonium phosphate, diammonium hydrogen phosphate, ammonium phosphate, phosphoric acid and ammonium hypophosphite.

[0013] In one embodiment of the present invention, the acid in the acid solution is selected from sulfuric acid and / or nitric acid.

[0014] In one embodiment of the present invention, the concentration of the acid solution is 15wt%~35wt%.

[0015] In one embodiment of the present invention, the high molecular polymer is polyvinyl pyrrolidone.

[0016] In one embodiment of the present invention, the carbon source is selected from one or more of glucose, citric acid, sucrose, oxalic acid, malonic acid, malic acid and mandelic acid.

[0017] In one embodiment of the present invention, the solvent is selected from one or more of water, anhydrous ethanol, acetic acid, hexafluoroisopropanol, chloroform and tetrahydrofuran.

[0018] In one embodiment of the present invention, the molar ratio of sodium in the sodium source, vanadium in the vanadium source and phosphorus in the phosphorus source is 3:2:3.

[0019] In one embodiment of the present invention, the mass ratio of the carbon source to the sodium vanadium phosphate in the sodium vanadium phosphate composite carbon nanofiber material is 0.5-1.5:100, and the mass ratio of the high molecular polymer to the sodium vanadium phosphate in the sodium vanadium phosphate composite carbon nanofiber material is 2-5:1.

[0020] In one embodiment of the present invention, the conditions for the electrospinning are: the voltage is 10KV~15KV, the distance between the filament outlet and the receiver in the electrospinning device is 12cm~20cm; the spinning speed is 0.1mm / min~0.5mm / min, and the rotation speed of the receiver is 4m / h~8m / h.

[0021] In one embodiment of the present invention, the conditions of the primary heat treatment are as follows: the heating and sintering temperature is 600°C~1000°C, the heating and sintering time is 4h~20h, the heating rate of the heating and sintering is 1°C / min~10°C / min, and the gas atmosphere for heating and sintering includes a mixture of argon and hydrogen.

[0022] In one embodiment of the present invention, the volume ratio of argon gas to hydrogen gas is 85:5-95:5.

[0023] In one embodiment of the present invention, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x In the step of mixing the mesogenic material, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x The mass ratio of the mesogen material is 100:0.1~0.4.

[0024] In one embodiment of the present invention, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x In the step of mixing the mesogenic materials, the mixing method is ball milling, the ball milling speed is 250r / min~750r / min, and the ball milling time is 1h~6h.

[0025] In one embodiment of the present invention, the conditions of the secondary heat treatment are: sintering temperature of 200°C~550°C, sintering time of 3h~10h, heating rate of 1°C / min~10°C / min, and the gas in the gas atmosphere for heating and sintering is one or more of helium, argon and nitrogen.

[0026] The second object of the present invention is to provide a positive electrode material, including a sodium vanadium phosphate composite carbon nanofiber material and a conductive mesogen coating layer coated on the surface of the sodium vanadium phosphate composite carbon nanofiber material, that is, conductive mesogen@sodium vanadium phosphate / carbon nanofiber material, "@" represents coating.

[0027] In one embodiment of the present invention, the conductive mesogen wrapping layer comprises a conductive mesogen material, and the molecular formula of the conductive mesogen material is M2O x ; wherein, M is one or more of Zn, Ce, Ti, Cu, Fe, W, Pb and Cd, and x is the valence state of M.

[0028] The third object of the present invention is to provide a positive electrode sheet, which includes a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, and the positive electrode active material layer includes the positive electrode material or the positive electrode material obtained by the above preparation method.

[0029] A fourth object of the present invention is to provide a sodium ion battery, comprising the positive electrode sheet.

[0030] The above technical solution of the present invention has the following advantages compared with the prior art:

[0031] M2O prepared by the present invention x Mesogen-coated carbon composite sodium vanadium phosphate nanofiber material M2O x @NVP / C has the following advantages:

[0032] 1. The sodium vanadium phosphate composite carbon fiber was prepared by electrospinning technology, which reduced the particle size of the sodium vanadium phosphate material and effectively shortened the migration path of sodium ions in the material. At the same time, the sodium vanadium phosphate was carbon-compounded, which simplified the synthesis steps and improved the conductivity of the sodium vanadium phosphate material to a certain extent, which can effectively improve the rate performance of the material.

[0033] 2. Prepared M2O with stable structure and excellent electronic conductivity x Mesogens, through the high surface polarity of carbon nanofibers and thermodynamic motion, transfer M2O x Mesogens adsorb on the NVP / C composite to form M2O x @NVP / C material, M2O x The mesogen coating can effectively inhibit the structural collapse of the material during high-rate charge and discharge, thereby stabilizing the structure of the material and improving the material's cycle stability and high-rate discharge characteristics.

[0034] In summary, the M2O prepared by the present invention x Mesogen-coated carbon composite sodium vanadium phosphate nanofiber material M2O x @NVP / C stabilizes the sodium vanadium phosphate material during the charge and discharge process, based on strengthening the ionic conductivity and electronic conductivity of the sodium vanadium phosphate material, and improves the rate performance and cycle stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0036] Figure 1 is the X-ray diffraction pattern of CeO2@NVP / C obtained in Example 1 of the present invention;

[0037] Figure 2 is a scanning electron microscope image of CeO2@NVP / C obtained in Example 1 of the present invention;

[0038] Figure 3 is a scanning electron microscope image of the CeO2 mesocrystal prepared in Example 1 of the present invention;

[0039] Figure 4 It is a scanning electron microscope image of the sodium vanadium phosphate prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0040] In order to solve the technical problems that the presence of [PO4] tetrahedral structure in the existing sodium vanadium phosphate material will hinder the transmission of electrons in the material, resulting in very low electronic conductivity, further restricting the reaction kinetics of the material, affecting the electrochemical properties of the material, etc.

[0041] The invention provides a positive electrode material and a preparation method and application thereof.

[0042] The present invention also provides a method for preparing a positive electrode material, comprising the following steps:

[0043] A sodium source, a vanadium source, a phosphorus source, a high molecular polymer, a carbon source and a solvent are mixed to obtain an electrospinning solution, and electrospinning is performed to obtain a nanofiber precursor, and a heat treatment is performed to obtain a sodium vanadium phosphate composite carbon nanofiber material;

[0044] The salt or oxide containing M is dispersed in an acid solution, the obtained mixed solution is reacted at 100°C to 200°C, and then the reaction liquid is separated into a solid phase, which is M2O x Mesogenic materials;

[0045] The sodium vanadium phosphate composite carbon nanofiber material and the M2O x Mesogen materials are mixed and subjected to secondary heat treatment to form M2O x Mesogen coating layer to obtain the positive electrode material;

[0046] Wherein, M is one or more of Zn, Ce, Ti, Cu, Fe, W, Pb and Cd, and x is the valence state of M.

[0047] Furthermore, the sodium source can be selected from conventional materials in the art, preferably but not limited to one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate and sodium nitrate;

[0048] Further, the vanadium source can be selected from conventional materials in the art, preferably but not limited to one or more of vanadium powder, vanadium pentoxide, vanadium trioxide and ammonium metavanadate;

[0049] Furthermore, the phosphorus source can be selected from conventional materials in the art, preferably but not limited to one or more of diammonium phosphate, diammonium hydrogen phosphate, ammonium phosphate, phosphoric acid and ammonium hypophosphite.

[0050] Furthermore, the high molecular polymer is polyvinyl pyrrolidone.

[0051] Furthermore, the carbon source is selected from one or more of glucose, citric acid, sucrose, oxalic acid, malonic acid, malic acid and mandelic acid.

[0052] Furthermore, the solvent is selected from one or more of water, anhydrous ethanol, acetic acid, hexafluoroisopropanol, chloroform and tetrahydrofuran.

[0053] Furthermore, the molar ratio of sodium in the sodium source, vanadium in the vanadium source and phosphorus in the phosphorus source is 3:2:3. The sodium in the sodium source is in excess of 3wt%-5wt%. Since there will be loss during the calcination process, sodium needs to be in excess, and the excess of the sodium source is a conventional operation in the art.

[0054] Furthermore, the mass ratio of the carbon source to the sodium vanadium phosphate in the sodium vanadium phosphate composite carbon nanofiber material is 0.5-1.5:100, and the mass ratio of the high molecular polymer to the sodium vanadium phosphate in the sodium vanadium phosphate composite carbon nanofiber material is 2-5:1.

[0055] Furthermore, the conditions of the electrospinning are as follows: the voltage is 10KV~15KV, the distance between the filament outlet and the receiver in the electrospinning device is 12cm~20cm; the spinning speed is 0.1mm / min~0.5mm / min, and the rotation speed of the receiver is 4m / h~8m / h.

[0056] Furthermore, the conditions of the primary heat treatment are as follows: the heating and sintering temperature is 600°C~1000°C, the heating and sintering time is 4h~20h, the heating rate of the heating and sintering is 1°C / min~10°C / min, and the gas atmosphere for heating and sintering includes a mixture of argon and hydrogen.

[0057] Furthermore, the volume ratio of argon to hydrogen is 85:5 to 95:5, preferably 90:5, 85:15, 95:5, etc., or any value between any two values.

[0058] Further, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x In the step of mixing the mesogenic material, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x The mass ratio of the mesogen material is 100:0.1-0.4, and preferably 100:0.1, 100:0.15, 100:0.3, 100:0.4, etc., or any value between any two values.

[0059] Furthermore, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x In the step of mixing the mesogenic materials, the mixing method is ball milling, the ball milling speed is 250r / min~750r / min, and the ball milling time is 1h~6h.

[0060] Furthermore, the conditions of the secondary heat treatment are: sintering temperature of 200°C~550°C, sintering time of 3h~10h, heating rate of 1°C / min~10°C / min, and the gas in the gas atmosphere for heating and sintering is one or more of helium, argon and nitrogen.

[0061] The second object of the present invention is to provide a positive electrode material, including a sodium vanadium phosphate composite carbon nanofiber material and a conductive mesogen coating layer coated on the surface of the sodium vanadium phosphate composite carbon nanofiber material, that is, conductive mesogen@sodium vanadium phosphate / carbon nanofiber material, "@" represents coating.

[0062] In one embodiment of the present invention, the conductive mesogen wrapping layer comprises a conductive mesogen material, and the molecular formula of the conductive mesogen material is M2O x ; wherein, M is one or more of Zn, Ce, Ti, Cu, Fe, W, Pb and Cd, and x is the valence state of M.

[0063] The present invention also provides a positive electrode sheet, which includes a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, the positive electrode active material layer includes a positive electrode material, a binder and a conductive agent, and the positive electrode material includes a conductive mesogen @ sodium vanadium phosphate / carbon nanofiber material and a conductive mesogen @ sodium vanadium phosphate / carbon nanofiber material obtained by the above-mentioned preparation method.

[0064] An embodiment of the present invention further provides a sodium ion battery, which includes the positive electrode sheet.

[0065] The present invention has no particular limitation on the method for preparing the sodium ion battery, and any battery preparation method known to those skilled in the art may be used.

[0066] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0067] Example 1

[0068] This embodiment provides a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C) and a preparation method and application thereof, as follows:

[0069] (I) Preparation method of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C) positive electrode material.

[0070] 1. Preparation steps of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C: weigh sodium acetate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate according to the molar ratio of Na:V:P=3:2:3, weigh citric acid according to the mass ratio of citric acid: sodium vanadium phosphate=0.75:100, use deionized water as solvent, place it on a magnetic stirrer and stir to dissolve, then add polyvinyl pyrrolidone, where the mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate is 3:1; continue stirring to form a uniform electrospinning solution. The electrospinning solution is extracted into a 5mL syringe, and the electrospinning needle is installed. The distance between the needle and the aluminum foil is 13.5cm, the voltage is 13KV; the electrospinning speed is 0.15mm / min; the speed of the receiver is 6m / h, and a one-dimensional nanofiber precursor is prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C was obtained.

[0071] 2. Preparation steps of CeO2 mesogenic material: Disperse CeO2 in 5 mol / L concentrated sulfuric acid under stirring to obtain Ce2(SO4)3 acid solution, and stir for 3.5 hours to obtain a mixed solution; then pour the mixed solution into a reactor, place it in an oven at 180°C, and react for 20 hours; after the reaction is completed, naturally cool to obtain a white precipitate, wash it with anhydrous ethanol 5 times, and then centrifuge it, and then place the separated product in a forced air drying oven at 80°C and dry it for 10 hours to obtain CeO2 mesogenic material. The structural characterization is shown in Figure 3 ,Depend on Figure 3 It can be seen that the prepared CeO2 mesogens are in the form of particles with a size distribution of 25nm~50nm.

[0072] 3. Preparation steps of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C): The sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C obtained in step 1 and the CeO2 mesogen material prepared in step 2 are placed in a ball mill with a rotation speed of 500r / min for 4.5h according to a mass ratio of 100:0.4 to obtain a uniformly mixed precursor powder; then the uniformly mixed powder is placed in a tubular furnace (nitrogen atmosphere condition) with a heating rate of 5℃ / min and subjected to secondary heat treatment at 450℃ for 8h to obtain a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C). The structural characterization is shown in Figure 1-Figure 2 , Figure 2 It can be seen that a layer of nano-sized granular mesogen material is attached to the carbon composite sodium vanadium phosphate nanofibers, indicating that the mesogens are coated on the carbon composite sodium vanadium phosphate nanofibers to form a mesogen-coated carbon composite sodium vanadium phosphate nanofiber material.

[0073] (II) Application of materials

[0074] The preparation of sodium ion batteries is as follows:

[0075] The CeO2@NVP / C composite material, binder PVDF and conductive carbon black super p were ground evenly according to the mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0076] (III) Performance test

[0077] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 1C 200th cycle, and 1C 500th cycle capacity retention of the material in the sodium ion battery. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the CeO2@NVP / C composite material prepared in this embodiment are shown in Table 1.

[0078] Example 2

[0079] This embodiment provides a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber (CeO2@NVP / C) positive electrode material and a preparation method and application thereof, as follows:

[0080] (I) Preparation method of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C).

[0081] 1. Preparation steps of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C: weigh sodium acetate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate according to the molar ratio of Na:V:P=3:2:3, weigh citric acid according to the mass ratio of citric acid: sodium vanadium phosphate=0.75:100, use deionized water as solvent, place it on a magnetic stirrer and stir to dissolve, and then add polyvinyl pyrrolidone. The mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate is 3:1; continue stirring to form a uniform electrospinning solution. Draw the electrospinning solution into a 5mL syringe, install the electrospinning needle, the distance between the needle and the aluminum foil is 13.5cm, the voltage is 13KV; the electrospinning speed is 0.15mm / min; the speed of the receiver is 6m / h, and a one-dimensional nanofiber precursor is prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C was obtained.

[0082] 2. Preparation steps of CeO2 mesogenic material: Under stirring conditions, disperse CeO2 in 5 mol / L concentrated sulfuric acid to obtain an acid solution of Ce2(SO4)3, and stir for 3.5 hours to obtain a mixed solution; then pour the mixed solution into a reactor, place it in an oven at 180°C, and react for 20 hours; after the reaction is completed, naturally cool it to obtain a white precipitate, wash it with anhydrous ethanol for 5 times, and then centrifuge it, and then place the separated product in a forced air drying oven at 80°C and dry it for 10 hours to obtain CeO2 mesogenic material.

[0083] 3. Preparation steps of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C): The sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C obtained in step 1 and the CeO2 mesogen material prepared in step 2 are placed in a ball mill at a speed of 500 r / min for 4.5 hours at a mass ratio of 100:0.25 to obtain a uniformly mixed precursor powder; the uniformly mixed powder is then placed in a tubular furnace (nitrogen atmosphere conditions) with a heating rate of 5°C / min for a secondary heat treatment at 450°C for 8 hours to obtain a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C).

[0084] (II) Application of materials

[0085] The preparation of sodium ion batteries is as follows:

[0086] The CeO2@NVP / C composite material, binder PVDF and conductive carbon black super p were ground evenly according to the mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0087] (III) Performance test

[0088] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 1C 200th cycle, and 1C 500th cycle capacity retention of the material in the sodium ion battery. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the CeO2@NVP / C composite material prepared in this embodiment are shown in Table 1.

[0089] Example 3

[0090] This embodiment provides a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber (CeO2@NVP / C) cathode material and a preparation method and application thereof, as follows:

[0091] (I) Preparation method of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C).

[0092] 1. Preparation steps of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C: weigh sodium acetate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate according to the molar ratio of Na:V:P=3:2:3, weigh citric acid according to the mass ratio of citric acid: sodium vanadium phosphate=0.75:100, use deionized water as solvent, place it on a magnetic stirrer and stir to dissolve, then add polyvinyl pyrrolidone, where the mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate is 3:1, and continue to stir to form a uniform electrospinning solution. The electrospinning solution is extracted into a 5mL syringe, and the electrospinning needle is installed. The distance between the needle and the aluminum foil is 13.5cm, the voltage is 13KV; the electrospinning speed is 0.15mm / min; the speed of the receiver is 6m / h, and a one-dimensional nanofiber precursor is prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C was obtained.

[0093] 2. Preparation steps of CeO2 mesogenic material: Under stirring conditions, disperse CeO2 in 5 mol / L concentrated sulfuric acid to obtain an acid solution of Ce2(SO4)3, and stir for 3.5 hours to obtain a mixed solution; then pour the mixed solution into a reactor, place it in an oven at 180°C, and react for 20 hours; after the reaction is completed, naturally cool it to obtain a white precipitate, wash it with anhydrous ethanol for 5 times, and then centrifuge it, and then place the separated product in a forced air drying oven at 80°C and dry it for 10 hours to obtain CeO2 mesogenic material.

[0094] 3. Preparation steps of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C): The sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C obtained in step 1 and the CeO2 mesogen material prepared in step 2 are placed in a ball mill at a rotation speed of 500r / min for 4.5h in a mass ratio of 100:0.1 to obtain a uniformly mixed precursor powder; and then the uniformly mixed powder is placed in a tubular furnace (nitrogen atmosphere condition) with a heating rate of 5℃ / min for a secondary heat treatment at 450℃ for 8h to obtain a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (CeO2@NVP / C).

[0095] (II) Application of materials

[0096] The preparation of sodium ion batteries is as follows:

[0097] The CeO2@NVP / C composite material, binder PVDF and conductive carbon black super p were ground evenly according to the mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0098] (III) Performance test

[0099] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 1C 200th cycle, and 1C 500th cycle capacity retention of the material in the sodium ion battery. Under the conditions of a discharge cut-off voltage of 2.0 V and a charge cut-off voltage of 4.0 V, the physical and chemical properties test results of the CeO2@NVP / C composite material prepared in this embodiment are shown in Table 1.

[0100] Example 4

[0101] This embodiment provides a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber (TiO2@NVP / C) positive electrode material and a preparation method and application thereof, as follows:

[0102] (I) Preparation method of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C.

[0103] 1. Preparation steps of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C: weigh sodium carbonate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate according to the molar ratio of Na:V:P=3:2:3, weigh citric acid according to the mass ratio of citric acid: sodium vanadium phosphate=0.75:100, use deionized water as solvent, place it on a magnetic stirrer and stir to dissolve, then add polyvinyl pyrrolidone, where the mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate is 3:1, continue to stir to form a uniform electrospinning solution. The electrospinning solution is extracted into a 5mL syringe, and the electrospinning needle is installed. The distance between the needle and the aluminum foil is 13.5cm, the voltage is 12KV; the electrospinning speed is 0.15mm / min; the speed of the receiver is 6m / h, and a one-dimensional nanofiber precursor is prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C was obtained.

[0104] 2. Preparation steps of TiO2 mesogenic material: Under stirring conditions, disperse TiO2 in 5 mol / L concentrated sulfuric acid to obtain an acid solution of Ti(SO4)2, and stir for 3.5 hours to obtain a mixed solution; then pour the mixed solution into a reactor, place it in an oven at 180°C, and react for 18 hours; after the reaction is completed, naturally cool it to obtain a white precipitate, wash it with anhydrous ethanol for 5 times, and then centrifuge it, and then place the separated product in an 80°C forced drying oven and dry it for 10 hours to obtain TiO2 mesogenic material.

[0105] 3. Preparation steps of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (TiO2@NVP / C): The sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C obtained in step 1 and the CeO2 mesogen material prepared in step 2 are placed in a ball mill at a rotation speed of 500r / min for 4.5h in a mass ratio of 100:0.15 to obtain a uniformly mixed precursor powder; and then the uniformly mixed powder is placed in a tubular furnace (nitrogen) with a heating rate of 5℃ / min for a secondary heat treatment at 550℃ for 10h to obtain a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber (TiO2@NVP / C) material.

[0106] (II) Application of materials

[0107] The preparation of sodium ion batteries is as follows:

[0108] The TiO2@NVP / C composite material, binder PVDF and conductive carbon black super p were ground evenly in a mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0109] (III) Performance test

[0110] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 0.1C 200th cycle, and 0.1C 500th cycle capacity retention in sodium ion batteries. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the TiO2@NVP / C composite material prepared in this embodiment are shown in Table 1.

[0111] Example 5

[0112] This embodiment provides a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber (ZnO@NVP / C) positive electrode material and a preparation method and application thereof, as follows:

[0113] (I) Preparation method of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (ZnO@NVP / C).

[0114] 1. Preparation steps of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C: weigh sodium carbonate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate according to the molar ratio of Na:V:P=3:2:3, weigh citric acid according to the mass ratio of citric acid: sodium vanadium phosphate=0.65:100, use deionized water as solvent, place it on a magnetic stirrer and stir to dissolve, then add polyvinyl pyrrolidone, where the mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate is 3:1, and continue to stir to form a uniform electrospinning solution. The electrospinning solution is extracted into a 5mL syringe, and the electrospinning needle is installed. The distance between the needle and the aluminum foil is 13.5cm, the voltage is 12KV; the electrospinning speed is 0.15mm / min; the speed of the receiver is 6m / h, and a one-dimensional nanofiber precursor is prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C was obtained.

[0115] 2. Preparation steps of ZnO mesogenic material: Under stirring conditions, ZnO is dispersed in 5 mol / L concentrated sulfuric acid to obtain an acid solution of ZnSO4, and the solution is stirred for 3.5 hours to obtain a mixed solution; the mixed solution is poured into a reactor, placed in an oven at 180°C, and reacted for 18 hours; after the reaction is completed, the white precipitate is naturally cooled to obtain a white precipitate, which is washed with anhydrous ethanol for 5 times and then centrifuged, and the separated product is placed in an 80°C forced air drying oven and dried for 10 hours to obtain a ZnO mesogenic material.

[0116] 3. Preparation steps of conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (ZnO@NVP / C): The sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C obtained in step 1 and the ZnO mesogen material prepared in step 2 are placed in a ball mill with a rotation speed of 500 r / min for 4.5 hours at a mass ratio of 100:0.15 to obtain a uniformly mixed precursor powder; and then the uniformly mixed powder is placed in a tubular furnace (nitrogen) with a heating rate of 5°C / min for a secondary heat treatment at 550°C for 10 hours to obtain a conductive mesogen-coated carbon composite sodium vanadium phosphate nanofiber material (ZnO@NVP / C).

[0117] (II) Application of materials

[0118] The preparation of sodium ion batteries is as follows:

[0119] The ZnO@NVP / C composite material, binder PVDF and conductive carbon black super p were ground evenly in a mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0120] (III) Performance test

[0121] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 1C 200th cycle, and 1C 500th cycle capacity retention of the material in the sodium ion battery. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the ZnO@NVP / C composite material prepared in this embodiment are shown in Table 1.

[0122] Comparative Example 1

[0123] This comparative example provides a sodium vanadium phosphate NVP and a preparation method and application thereof, as follows:

[0124] (I) Preparation method of sodium vanadium phosphate NVP.

[0125] Preparation steps of sodium vanadium phosphate NVP: sodium carbonate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate are weighed according to the molar ratio of Na:V:P=3:2:3, and are placed in a ball mill at 500r / min for 10 hours to make them uniform. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the mixture is heated to 850°C at a heating rate of 5°C / min for 12 hours, and then cooled in the furnace to obtain sodium vanadium phosphate NVP material. The structural characterization is shown in FIG. Figure 4 .

[0126] (II) Application of materials

[0127] Preparation of sodium ion battery: NVP material, binder PVDF and conductive carbon black super p were ground evenly according to the mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0128] (III) Performance test

[0129] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 1C 200th cycle, and 1C 500th cycle capacity retention of the material in the sodium ion battery. Under the conditions of a discharge cut-off voltage of 2.0 V and a charge cut-off voltage of 4.0 V, the physical and chemical properties test results of the NVP material prepared in this embodiment are shown in Table 1.

[0130] Comparative Example 2

[0131] This comparative example provides a sodium vanadium phosphate nanofiber positive electrode material NVP and its preparation method and application, as follows:

[0132] (I) Preparation method of sodium vanadium phosphate nanofiber positive electrode material NVP.

[0133] Preparation steps of sodium vanadium phosphate nanofiber positive electrode material NVP: weigh sodium carbonate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate according to the molar ratio of Na:V:P=3:2:3, use deionized water as solvent, place them on a magnetic stirrer and stir to dissolve, then add polyvinyl pyrrolidone, where the mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate is 3:1, and continue stirring to form a uniform electrospinning solution. The electrospinning solution is extracted into a 5mL syringe, and the electrospinning needle is installed. The distance between the needle and the aluminum foil is 13.5cm, the voltage is 12KV; the electrospinning speed is 0.15mm / min; the speed of the receiver is 6m / h, and a one-dimensional nanofiber precursor is prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate nanofiber positive electrode material NVP was obtained.

[0134] (II) Application of materials

[0135] The preparation of sodium ion batteries is as follows:

[0136] Sodium vanadium phosphate nanofiber material, binder PVDF and conductive carbon black super p were ground evenly in a mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0137] (III) Performance test

[0138] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 1C 200th cycle, and 1C 500th cycle capacity retention in sodium ion batteries. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the sodium vanadium phosphate nanofiber material prepared in this embodiment are shown in Table 1.

[0139] Comparative Example 3

[0140] This comparative example provides a sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C and its preparation method and application, as follows:

[0141] (I) Preparation method of sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C.

[0142] Sodium carbonate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate were weighed according to the molar ratio of Na:V:P=3:2:3, and citric acid was weighed according to the mass ratio of citric acid: sodium vanadium phosphate=0.65:100. Deionized water was used as the solvent, and it was placed on a magnetic stirrer for stirring and dissolving, and then polyvinyl pyrrolidone with a mass ratio of polymer: sodium vanadium phosphate=3:1 was added, and continued to stir to form a uniform electrospinning solution. The electrospinning solution was extracted into a 5mL syringe, and the electrospinning needle was installed. The distance between the needle and the aluminum foil was 13.5cm, the voltage was 12KV; the electrospinning speed was 0.15mm / min; the speed of the receiver was 6m / h, and a one-dimensional nanofiber precursor was prepared. In an atmosphere of a mixed gas with a volume concentration of 95% argon and 5% hydrogen, the obtained nanofiber precursor was placed in a tubular furnace for heat treatment, wherein the heating rate was 4°C / min, heated to 850°C for heat treatment for 12 hours, and after cooling in the furnace, sodium vanadium phosphate composite carbon nanofiber positive electrode material NVP / C was obtained.

[0143] (II) Application of materials

[0144] The preparation of sodium ion batteries is as follows:

[0145] The NVP / C composite material, binder PVDF and conductive carbon black super p were ground evenly in a mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ for 1h in a blast drying oven, and then dried at 120℃ for 12h in a vacuum drying oven; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0146] (III) Performance test

[0147] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 0.1C 200th cycle, and 0.1C 500th cycle capacity retention in sodium ion batteries. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the NVP / C composite material prepared in this embodiment are shown in Table 1.

[0148] Comparative Example 4

[0149] This comparative example provides a sodium vanadium phosphate nanofiber positive electrode material NVP / C and a preparation method and application thereof, as follows:

[0150] (I) Preparation method of sodium vanadium phosphate nanofiber positive electrode material NVP / C.

[0151] 1. Sodium carbonate (3% excess), vanadium pentoxide, and ammonium dihydrogen phosphate were weighed according to the molar ratio of Na:V:P=3:2:3, and deionized water was used as the solvent. They were placed on a magnetic stirrer and stirred to dissolve, and then polyvinyl pyrrolidone was added, wherein the mass ratio of polyvinyl pyrrolidone to sodium vanadium phosphate was 3:1, and stirring was continued to form a uniform electrospinning solution. The electrospinning solution was extracted into a 5mL syringe, and the electrospinning needle was installed. The distance between the needle and the aluminum foil was 13.5cm, and the voltage was 12KV; the electrospinning speed was 0.15mm / min; the speed of the receiver was 6m / h, and a one-dimensional nanofiber precursor was prepared. The obtained nanofiber precursor was placed in a tubular furnace with a heating rate of 4℃ / min and a 95% argon + 5% hydrogen atmosphere for heat treatment at 850℃ for 12h, and the sodium vanadium phosphate nanofiber positive electrode material NVP was obtained after cooling with the furnace.

[0152] 2. While stirring the materials, disperse TiO2 in 5 mol / L concentrated sulfuric acid to obtain an acid solution of Ce2(SO4)3, and stir for 3.5 hours to obtain a mixed solution; then pour the mixed solution into a reactor, place it in an oven at 180°C, and react for 18 hours; after the reaction is completed, naturally cool it to obtain a white precipitate, wash it with anhydrous ethanol 5 times, and then centrifuge it, and then place the separated product in an 80°C forced drying oven and dry it for 10 hours to obtain TiO2 mesogenic material.

[0153] 3. The sodium vanadium phosphate nanofiber positive electrode material NVP obtained in step 1 and the TiO2 mesogen material prepared in step 2 are placed in a ball mill at a rotation speed of 500 r / min for 4.5 hours in a mass ratio of 100:0.15 to obtain a uniformly mixed precursor powder; the uniformly mixed powder is then placed in a tubular furnace (nitrogen) with a heating rate of 5°C / min for a secondary heat treatment at 550°C for 10 hours to obtain a conductive mesogen-coated sodium vanadium phosphate nanofiber (TiO2@NVP) material.

[0154] (II) Application of materials

[0155] The preparation of sodium ion batteries is as follows:

[0156] The TiO2@NVP composite material, binder PVDF and conductive carbon black super p were ground evenly in a mass ratio of 90:5:5, and then an appropriate amount of NMP was added to make a slurry, which was evenly coated on the pretreated aluminum foil, dried at 80℃ in a blast drying oven for 1h, and then dried at 120℃ in a vacuum drying oven for 12h; then cut into 14mm round positive electrode sheets with a cutting machine. A sodium metal sheet with a diameter of 14mm and a thickness of 0.2mm was used as the negative electrode, a 0.1mol / L sodium perchlorate / ethylene carbonate / dimethyl carbonate solution was used as the electrolyte, and a WhatmanGF / F glass fiber with a diameter of 16mm was used as the diaphragm. The CR2032 button battery was assembled in a glove box filled with high-purity argon.

[0157] (III) Performance test

[0158] The constant current charge and discharge mode was used to perform charge and discharge tests at different current densities. The test items included: 0.1C first cycle charge and discharge, 1C / 5C / 10C / 20C rate discharge, 0.1C 200th cycle, and 0.1C 500th cycle capacity retention in sodium ion batteries. Under the conditions of a discharge cut-off voltage of 2.0V and a charge cut-off voltage of 4.0V, the physical and chemical properties test results of the TiO2@NVP composite material prepared in this comparative example are shown in Table 1.

[0159] Table 1 Electrochemical performance of Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4

[0160]

[0161] Note: “ / ” indicates that the charge and discharge curves are abnormal and charging and discharging cannot be performed.

[0162] As shown in Table 1, (1) in Examples 1 to 3, different contents of CeO2 mesogens were used for coating under the same main material type. The more the coating content, the lower the discharge capacity of the material, but the better the rate performance and cycle stability; the less the coating content, the higher the discharge capacity of the material, but it will affect the rate and cycle performance of the material. Compared with Comparative Example 1, due to the presence of the mesogen coating layer and carbon, the 0.1C first cycle discharge capacity of Examples 1-5 decreased slightly, but the 1C discharge capacity and 1C200 cycle capacity retention rate were significantly improved. The material of Comparative Example 1 could not even meet the charge and discharge at a rate of 5C, and could not complete 500 cycles of charge and discharge cycles, indicating that the mesogen material coated sodium vanadium phosphate carbon composite nanofibers prepared by the present invention can effectively improve the rate performance and cycle performance of the sodium vanadium phosphate positive electrode material.

[0163] (2) Compared with Example 4 and Comparative Example 4, the difference lies in whether the sodium vanadium phosphate is carbon-compounded. Combined with the data in Table 1, Example 4 adopts the method of coating the sodium vanadium phosphate carbon composite nanofiber with mesogens. Due to the presence of carbon, the reversible capacity of the sacrificial material is partially increased, but the rate performance and capacity retention rate of the material are improved, especially the high-rate discharge performance. Compared with Comparative Example 3, the difference between Example 5 and Comparative Example 3 lies in whether there is a mesogen material coating layer. The data in the table show that after the mesogen material is coated with the sodium vanadium phosphate carbon composite nanofiber, the rate performance and capacity retention rate of the material are greatly improved, indicating that the coating of the mesogen material can effectively inhibit the structural collapse of the material caused by the high-rate charge and discharge process, thereby stabilizing the structure of the material and improving the material's cycle stability and high-rate discharge characteristics.

[0164] (3) Comparative Example 1 is an amorphous sodium vanadium phosphate material synthesized by a conventional solid phase method. Compared with the sodium vanadium phosphate nanofibers synthesized by electrospinning in Comparative Example 2, under the condition of 1C rate discharge, the capacity decreases, but both cannot meet the high rate discharge performance of the material. This shows that the nano-sizing of sodium vanadium phosphate can improve the electrochemical performance of the material to a certain extent. Comparative Example 3 is a sodium vanadium phosphate carbon composite nanofiber NVP / C prepared by the method of the present invention. Compared with Comparative Example 2, the compounding of carbon materials is increased, which improves the rate performance and capacity retention rate of the material to a certain extent, but it is still not very ideal under the condition of high rate discharge. Comparative Example 4 is a sodium vanadium phosphate nanofiber M2O coated with mesogens. x @NVP, the lack of carbon material compounding also improves the rate discharge performance of the material, but this method, like the single carbon compound, has limited improvements in high-rate discharge and capacity retention.

[0165] In summary, the present invention adopts mesocrystal-coated sodium vanadium phosphate carbon composite nanofiber M2O x @NVP / C material method, by using the encapsulation of mesogen materials and coordinating sodium vanadium phosphate carbon composite nanofibers, improves the electronic conductivity and structural stability of the material, greatly improving the material's high-rate discharge performance and cycle stability.

[0166] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: A sodium source, a vanadium source, a phosphorus source, a high molecular polymer, a carbon source and a solvent are mixed to obtain an electrospinning solution, and electrospinning is performed to obtain a nanofiber precursor, and a heat treatment is performed to obtain a sodium vanadium phosphate composite carbon nanofiber material; The salt or oxide containing M is dispersed in an acid solution, the obtained mixed solution is reacted at 100°C to 200°C, and then the reaction liquid is separated into a solid phase, which is M2O x Mesogenic materials; The sodium vanadium phosphate composite carbon nanofiber material and the M2O x Mesogen materials are mixed and subjected to secondary heat treatment to form M2O x Mesogen coating layer to obtain the positive electrode material; Wherein, M is one or more of Zn, Ce, Ti, Cu, Fe, W, Pb and Cd, and x is the valence state of M.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon source to the sodium vanadium phosphate in the sodium vanadium phosphate composite carbon nanofiber material is 0.5-1.5:100, and the mass ratio of the high molecular polymer to the sodium vanadium phosphate in the sodium vanadium phosphate composite carbon nanofiber material is 2-5:

1.

3. The preparation method according to claim 1, characterized in that: The electrospinning conditions are as follows: the voltage is 10KV~15KV, the distance between the outlet and the receiver in the electrospinning device is 12cm~20cm; the spinning speed is 0.1mm / min~0.5mm / min, and the rotation speed of the receiver is 4m / h~8m / h; The conditions of the primary heat treatment are as follows: the heating and sintering temperature is 600°C to 1000°C, the heating and sintering time is 4h to 20h, the heating rate of the heating and sintering is 1°C / min to 10°C / min, and the gas atmosphere for the heating and sintering includes a mixed gas of argon and hydrogen.

4. The preparation method according to claim 1, characterized in that: The sodium vanadium phosphate composite carbon nanofiber material and the M2O x In the step of mixing the mesogenic material, the sodium vanadium phosphate composite carbon nanofiber material and the M2O x The mass ratio of the mesogen material is 100:0.1~0.

4.

5. The preparation method according to claim 1, characterized in that: The acid in the acid solution is selected from sulfuric acid and / or nitric acid; the concentration of the acid solution is 15wt%~35wt%.

6. The preparation method according to claim 1, characterized in that: The conditions of the secondary heat treatment are as follows: sintering temperature of 200°C to 550°C, sintering time of 3h to 10h, heating rate of 1°C / min to 10°C / min, and the gas in the gas atmosphere for heating and sintering is one or more of helium, argon and nitrogen; The sodium vanadium phosphate composite carbon nanofiber material and the M2O x In the step of mixing the mesogenic materials, the mixing method is ball milling, the ball milling speed is 250r / min~750r / min, and the ball milling time is 1h~6h.

7. A positive electrode material, characterized in that: The invention comprises a sodium vanadium phosphate composite carbon nanofiber material and a conductive mesogen wrapping layer wrapped on the surface of the sodium vanadium phosphate composite carbon nanofiber material; the conductive mesogen wrapping layer comprises a conductive mesogen material, and the molecular formula of the conductive mesogen material is M2O x ; wherein, M is one or more of Zn, Ce, Ti, Cu, Fe, W, Pb and Cd, and x is the valence state of M.

8. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material obtained by the preparation method of any one of claims 1 to 6 or the positive electrode material described in claim 7.

9. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet described in claim 8.

Citation Information

Patent Citations

  • Lithium ion cell anode material lithium vanadium phosphate and preparation method thereof

    CN101145611A

  • Method for preparing Na3V2(PO4)3 nanofiber cathode material

    CN109950536A